ANALISA IMBALAN PASCA KERJA BERDASARKAN SAK ETAP DAN PENGARUHNYA TERHADAP OPINI AUDITOR ATAS LAPORAN KEUANGAN - Nazarudin, Nazarudin; Adang, Ferry; Suseno, Joko (Jurnal Ekonomi Integra, 2025)
This study aims to analyze the implementation of post-employment benefit obligations at Koperasi Sinar Andalas and their impact on the auditor's opinion on financial statements. According to Law No. 13 of 2003 on Manpower, companies are required to provide post-employment benefits to employees who experience termination of employment. These benefits include severance pay, long-service awards, and compensation for workers’ rights related to pension benefits. In Chapter 23 of SAK ETAP, post-employment benefit obligations and expenses must be recognized due to their material nature. However, many companies, especially those not publicly listed, fail to implement this requirement. Auditors play a crucial role in ensuring compliance with these obligations, as post-employment benefits can significantly affect the opinion on financial statements. This study uses a quantitative approach with the Projected Unit Credit Method to calculate post-employment benefit obligations. The results show that Koperasi Sinar Andalas has not implemented post-employment benefit obligations in accordance with SAK ETAP. Consequently, their financial statements received a qualified opinion due to the material liabilities that were not recognized..